Solar-wind intelligent street lighting - Tan, Ming Li. (2010)
Feasibility study and hardware implementation of an intelligent street lighting system, based on solar and wind as primary energy sources, battery as energy storage together with high-brightness light emitting diodes (HB-LED) lamp module as light source, for urban cities like Singapore were evaluated in this project and discussed in this report. This lighting system using solar and wind renewable energy resources, is evaluated as a substitute of the current street lighting system using electricity from the power grid in Singapore when most of those street lamps are reaching their expected lifespan of 25-30 years of service in the next 5 to 10 years. The same intelligent street lighting system is also applicable for remote area. The design of LED fixture to replace current used high pressure sodium (HPS) lamp in street lighting system is studied in this project. The street lighting standard and requirement as detailed by Singapore Land and Transport Authority (LTA) are outlined taking into the account the expected lifespan and color quality of the street lighting system. LED driver and brightness experimental result are presented. Sizing of battery and solar panel capacities will be illustrated for the new street lighting system. The procedure of design a monitoring system for the new solar-wind hybrid street lighting system is also presented. The prototype intelligent street lighting system was assembled using whatever available components or parts (such as the solar PV panels, permanent magnet generator, batteries etc)in the laboratory. Such prototype system was meant for a proof-of-concept design and did not mean to provide the ultimate best performance as would be expected if proper system design was carried with selected parts to suit the design requirements, Environmental factor such as wind speed and direction as well as solar radiation level were monitored by the a small weather station located next to the performance data of the vertical axis wind turbine (VAWT) was collected by data logger and present in this report. The data collected will be used to analysis the efficiency of the VAWT designed by our team.